2008
DOI: 10.1089/lap.2007.0022
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Spleen-Preserving Laparoscopic Distal Pancreatectomy and Concomitant Cholecystectomy in Male Patient with Solid Pseudopapillary Neoplasm of the Pancreas and Gallstone

Abstract: Solid pseudopapillary neoplasm is a rare pathologic condition in the pancreas. The origin of this tumor and characteristic biologic behavior are still under investigation. With the advances of laparoscopic surgery, laparoscopic pancreatic surgery has been accepted as a feasible, safe procedure. Especially, laparoscopic distal pancreatectomy is regarded as an appropriate treatment option for benign or borderline malignant pancreatic lesions. In addition, the frequency of spleen-preserving laparoscopic distal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The laparoscopic surgery is also an option to the SPN and depends on the lesion location in the pancreatic parenchyma, tumor size and experience of the surgical team. The safety is the same as the open surgery, in addition to offering better surgical field, less pain after surgery and faster recovery of the patient 7 , 13 , 14 . Cavallini et al demonstrated the efficacy of laparoscopy in 10 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic surgery is also an option to the SPN and depends on the lesion location in the pancreatic parenchyma, tumor size and experience of the surgical team. The safety is the same as the open surgery, in addition to offering better surgical field, less pain after surgery and faster recovery of the patient 7 , 13 , 14 . Cavallini et al demonstrated the efficacy of laparoscopy in 10 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although SPT is a rare pancreatic lesion with a benign and low‐grade malignant nature, it is well known to predominantly affect young women aged 25–35 years. In addition, considering that the most common location of this tumor is the tail of the pancreas , a minimally invasive approach is thought to be more appropriate than an open approach for managing SPT of the distal pancreas [9, 10] because laparoscopic distal pancreatectomy has been accepted as a safe and effective treatment modality to manage benign and borderline malignant tumors of the pancreas [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, staging and partial resections for benign and malignant diseases began with Bernheim, Cuschieri, Ishida, and Meyer Burg until, in 1994, the first laparoscopic pancreaticoduodenectomy was performed in a woman with chronic pancreatitis 1,3 . Since then, laparoscopic surgery has evolved in such a way that there are practically no contraindications or limitations regarding the type of pathologies that can be resolved with this technique 13,14 . The results obtained with this type of procedure have been reported, and the vast majority agree that the minimally invasive technique in pancreaticobiliary surgery is highly effective 15,16 , and specially for distal pancreatic resections with or without splenic preservation, it is gaining great strength, and in numerous studies, it is the first option for diseases within this region of the pancreas [17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%